BIOELEMENTAL COMPOSITION OF FRUITS OF PODOPHYLLUM HEXANDRUM - S. P. Lukashuk (Фармация и фармакология (Пятигорск), 2015)
Six macro and nine microelements were detected in fruits of Podophyllum hexandrum using a method of atomic emission spectroscopy. The content of some microelements prevails in seeds comparing with pericarp. The data received can be used for new effective phytopreparations development